Insufficiency of digital health services in a rural Mexican population - Fernando Castro Cota; Aray Cabello Cabrera (Edumecentro)
Background: Historically, rural regions of Mexico have been characterized by a lack of communication infrastructure and social isolation, which contributes to difficulties in digital health and education services. Objective: to determine the need for digital health services for health information and education in the rural population of San Felipe, in the municipality of Mexicali, Mexico. Methods: qualitative research was developed in San Felipe, rural population of the municipality of Mexicali, Mexico, in the period 2021 to 2023. Theoretical methods were used: analysis-synthesis, inductive-deductive and historical-logical; empirical methods: questionnaire to residents; and mathematical-statistical methods for the analysis of the data obtained. Results: within the sample chosen for the research, the predominant sex was male (56.25 %) and with a high school diploma (37.50 %); 71.87 % said that Internet connectivity was not acceptable, 81.09 % connected through cellular phones and only 6.25 % used it for health advice. 71.87% of the users say that the health service in their community is bad and they believe that it would improve in terms of health promotion, disease prevention and even assistance if connectivity had greater coverage. Conclusions: the need for digital services for health information and education was determined in a rural population in the municipality of Mexicali, Mexico. Given that medical care is rated as deficient, the use of information and communication technologies could be a viable and prudent alternative to make up for the shortcomings diagnosed.